Formulasi Permen Jeli Vegan Sari Buah Nanas, Lemon, Bunga Kol, dan Umbi Bit Merah dengan Konsentrasi Karagenan - Putri, Elita Mahda Gatra; Wahyudi, Vritta Amroini; Warkoyo, Warkoyo; Harini, Noor; Husna, Afifa (Food Technology and Halal Science Journal, 2024)
Abstract. The vegan lifestyle is currently trending and growing very rapidly. The need for nutrients produced by plant-based products is an important concern of the community. One product that has the potential to become a vegan product is vegan jelly candy. The purpose of this study was to determine the formulation and potential of jelly candy as a vegan product seen from the parameters of water content, fiber content, pH, water activity, vitamin C content, antioxidant activity, and organoleptic (color, aroma, taste, texture, overall). The research method used was a Factorial Complete Randomized Design with 2 factors, namely fruit and vegetable formulations and carrageenan concentration, 6 treatments, and 2 replicates. The analysis used was Analysis of Variance at the 5% level. Further tests using Duncan Multiple Range Test at the 5% level for samples that give a real effect. The standard requirements for vegan jelly candy products are in SNI 3547.2-2008. The overall acceptable vegan jeli candy product for panelists was N2K2 (60% Pineapple: 6% Lemon: 17% Cauliflower: 17% Red Beetroot; 2.25% Carrageenan) with a moisture content of 10.47±5.54%; crude fiber content of 6.88±1.39%; pH 3.83±0.12; Aw 0.81±0.02; vitamin C content of 20.77±4.89%; antioxidant activity of 13.38±9.27%; organoleptic parameters of red-red very purple color; slightly fragrant aroma of jeli candy; sweet and sour taste; slightly chewy texture. Keywords: Nutrasetical; Antioxidant; Vitamin C Abstrak. Pola hidup vegan saat ini menjadi tren dan berkembang sangat pesat. Kebutuhan akan nutrisi yang dihasilkan produk nabati menjadi perhatian penting masyarakat. Salah satu produk yang berpotensi menjadi produk vegan yaitu permen jeli vegan. Tujuan penelitian ini untuk mengetahui formulasi dan potensi permen jeli sebagai produk vegan dilihat dari parameter kadar air, kadar serat, pH, aktivitas air, kadar vitamin C, aktivitas antioksidan, dan organoleptik (warna, aroma, rasa, tekstur, overall). Metode penelitian yang digunakan yaitu Rancangan Acak Lengkap Faktorial dengan 2 faktor yaitu formulasi buah dan sayur serta konsentrasi karagenan, 6 perlakuan, dan 2 kali ulangan. Analisis yang digunakan yaitu Analysis of Varians dengan taraf 5%. Uji lanjut menggunakan Duncan Multiple Range Test pada taraf 5% untuk sampel yang memberikan pengaruh nyata. Standar persyaratan produk permen jeli vegan ada pada SNI 3547.2-2008. Produk permen jeli vegan secara keseluruhan yang dapat diterima panelis N2K2 (60% Nanas: 6% Lemon: 17% Bunga Kol: 17% Bit Merah; 2,25% Karagenan) dengan kadar air 10,47±5,54%; kadar serat kasar 6,88±1,39%; pH 3,83±0,12 ; Aw 0,81±0,02; kadar vitamin C 20,77±4,89 mg/mL; aktivitas antioksidan 13,38±9,27%; parameter organoleptik warna merah-merah sangat ungu; aroma agak sedikit harum permen jeli; rasa manis dan asam; tekstur agak sedikit kenyal-kenyal. Kata Kunci: Nutrasetical; Antioksidan; Vitamin C